Analysis Of The Effect Of Local Original Revenue (PAD) And Capital Expenditure On Economic Growth In East Java Province 2015-2023 - Hastomo Deta Wardhana; Marseto; Anisa Fitria Utami (International Journal of Economics, Business and Innovation Research, 2026)
Regional economic growth is an important indicator of development performance in the era of fiscal decentralization. This study aims to analyze the effect of Local Own-Source Revenue (PAD) and capital expenditure on economic growth of in East Java Province during 2015–2023. This research employs a quantitative approach using multiple linear regression, with PAD and capital expenditure transformed into natural logarithms. The study uses secondary data obtained from the Central Statistics Agency and the Directorate General of Fiscal Balance. The results show that PAD does not have a significant partial effect on economic growth, while capital expenditure has a significant effect. However, simultaneously, PAD and capital expenditure significantly influence regional economic growth. These findings indicate that capital expenditure plays a more dominant role in promoting regional economic growth.